Evaluasi Pembelajaran Bahasa Arab dengan Memanfaatkan Aplikasi MiSK - Muhammad Rizal; Syihabuddin Syihabuddin; Mad‘ali Mad‘ali (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
This study aims to optimize the evaluation of Arabic learning by utilizing technological developments as a means of evaluation. On this occasion, the researcher chose the MiSK application as a model, which is a game-based learning application on Android, equipped with Arabic vocabulary, images, and audio, which was designed by one of the lecturers from Istanbul 29 Mayis University. Researchers use the data that has been obtained to conduct library research, link some problems with existing theories, and find relevant solutions for each problem obtained. Some of the problems related to this research are: 1) Advances in information technology require teachers to always provide interesting, intuitive, and interactive learning facilities. 2) The lack of Arabic language applications that can test the four basic language learning skills in one application. Of the existing problems, there are several solutions, one of which is by using the MiSK application. Teachers can easily provide an evaluation of Arabic learning which already contains four basic skills in one application